2014
DOI: 10.1890/13-0760.1
|View full text |Cite
|
Sign up to set email alerts
|

Insect mutualisms buffer warming effects on multiple trophic levels

Abstract: Abstract. Insect mutualisms can have disproportionately large impacts on local arthropod and plant communities and their responses to climatic change. The objective of this study was to determine if the presence of insect mutualisms affects host plant and herbivore responses to warming. Using open-top warming chambers at Harvard Forest, Massachusetts, USA, we manipulated temperature and presence of ants and Chaitophorus populicola aphids on Populus tremuloides host plants and monitored ant attendance and persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…In open-top warming experiments, populations of the aphid, Chaitophorus populicola, were higher when tended by mutualistic ants, regardless of temperature [139]. In their study, plant stress decreased with warming only when both ants and C. populicola aphids were associated in mutualistic Other guilds Temperate S. Korea Beetles Effect of temperature on communities [143] interactions, suggesting that such interspecific interactions could buffer the effects of warming on herbivore communities.…”
Section: Other Guildsmentioning
confidence: 90%
See 1 more Smart Citation
“…In open-top warming experiments, populations of the aphid, Chaitophorus populicola, were higher when tended by mutualistic ants, regardless of temperature [139]. In their study, plant stress decreased with warming only when both ants and C. populicola aphids were associated in mutualistic Other guilds Temperate S. Korea Beetles Effect of temperature on communities [143] interactions, suggesting that such interspecific interactions could buffer the effects of warming on herbivore communities.…”
Section: Other Guildsmentioning
confidence: 90%
“…Even though populations increased over this period, per capita rates of change were negatively associated with climate change variables in time series models. It appears that negative effects of climate change on population growth can be buffered by other ecological factors [135,139].…”
Section: Defoliatorsmentioning
confidence: 99%
“…In other work along the same elevational gradient, we found that natural enemy abundance and top‐down control of aphids ( A. varians feeding on C. angustifolium ) were greater at low elevations (Nelson, Pratt, et al, ). Predation and parasitism by invertebrates are often stronger at lower elevations (Roslin et al, ; Sam et al, ; Straw et al, ), and experimental warming has been found to directly affect the abundance of predators of other aphids ( Chaitophorus populicola ) feeding on aspen (Marquis, Del Toro, & Pelini, ). It is possible that natural enemy abundance also increased with aridity in our system, but we may not have detected such patterns because many flying natural enemies (e.g., parasitoid wasps) spend only brief amounts of time at aphid colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, elevated temperature increases insect overwintering, damage magnitude and range expansion 10 . Besides, climate change may significantly modify the dynamic interactions between plants and insects 11 . Temperature increase may facilitate the growth of herbivores through restraining the concentrations of several phenolic compounds in plant leaves 12 .…”
Section: Introductionmentioning
confidence: 99%